Mengkulik Makna Sakral Budaya Erau di Kutai Kartanegara Sebagai Simbol Persatu Mayarakat Adat Tenggarong - Fitri Nur Jannah; Muhammad Iqbal Birsyada (Yayasan Azhar Amanaa Yogyakarta, 2026)
This article examines the sacred meanings embedded in Erau culture in Kutai Kartanegara and explains how they become a symbol of unity for the Tenggarong indigenous community. The discussion focuses on the Erau celebration and the ritual symbols that represent the identity of the Kutai Sultanate, customary society, and the surrounding community. Through Peirce's semiotic perspective, the study interprets the connection between signs, objects, and meanings within the sequence of Erau rituals. The findings indicate that Erau is more than a cultural festival because it functions as a symbolic arena for affirming communal identity, strengthening solidarity, and preserving sacred narratives. Erau symbols also serve expressive, creative, psychological, and social functions for indigenous and wider communities in Tenggarong. These symbols show the relationship among the sultanate, customary community, and society as interconnected elements that support unity in Kutai Kartanegara.